Simulated effects of climate change on green gram production in Kitui County, Kenya - Mugo, Jane Wangui; Opijah, Franklin J.; Ngaina, Joshua; Karanja, Faith; Mburu, Mary (Frontiers in Sustainable Food Systems, 2023)
This study purposed to evaluate the impact of climate change on green gram yield, biomass and days to maturity under the baseline and future climate scenarios in Kitui County, Kenya. A field experiment was conducted during the March–April–May (MAM) and October–November–December (OND) planting seasons of 2018 and 2019 in the South Eastern Kenya University (SEKU) farm. Data on soil physical and chemical properties, daily climate data on rainfall, maximum and minimum temperature, and solar radiation, and green gram phenology dates were collected from the site and used in the calibration and validation of the APSIM model for four varieties of green gram, namely Biashara, Tosha, N26, and KS20 varieties. The calibrated green gram model captured the observed yield, biomass and days to maturity of the four varieties of green gram well. The calibrated green gram model was used to simulate the effects of climate change using daily climate data from an equal-weight ensemble of the nine CORDEX RCA4 models under the baseline scenario (1971 to 2000), and the future RCP 4.5 and 8.5 scenarios (2021 to 2050). During the MAM and OND seasons, a statistically significant decline in yield, biomass, and days to maturity is expected under both the RCP 4.5 and RCP 8.5 scenarios. The high variability in rainfall amount under both the RCP 4.5 and RCP 8.5 scenarios will translate to a lower yield and biomass. The increase in temperature under both the RCP 4.5 and RCP 8.5 scenarios will reduce the days to maturity for green grams in Kitui County. A decline in green gram yield is expected under future climate scenarios in one of the highly suitable zones for Kitui County, Kenya. Given that the government aims to revive farming in the ASALs by promoting climate-smart agriculture through planting drought-resistance crops, there is a need to develop green gram varieties which are more tolerant to the expected change in climate.